2014
DOI: 10.1038/modpathol.2014.37
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic and molecular analysis of disseminated appendiceal mucinous neoplasms: identification of factors predicting survival and proposed criteria for a three-tiered assessment of tumor grade

Abstract: Previous studies have demonstrated that the prognosis of disseminated mucinous appendiceal neoplasms is highly dependent upon tumor grade. Reflecting this, the 7th edition of the American Joint Committee on Cancer (AJCC) staging system now incorporates a three-tier grading system for prognostic staging of mucinous appendiceal tumors. However, the grading criteria are not well described. In order to address this issue, we evaluated clinicopathologic and molecular features of 219 cases from 151 patients with wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
120
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(130 citation statements)
references
References 28 publications
6
120
2
1
Order By: Relevance
“…These findings suggest the possible involvement of p53 during the progression of LAMN to MAC. Collectively, these findings are the first evidence that confirmed co-existence of genetically distinct low-grade and high-grade components within AMTs and possible transformations of MAC from LAMN within a single tumor, different from those that occurred during the recurrent process of the tumor [30].…”
Section: Discussionsupporting
confidence: 53%
“…These findings suggest the possible involvement of p53 during the progression of LAMN to MAC. Collectively, these findings are the first evidence that confirmed co-existence of genetically distinct low-grade and high-grade components within AMTs and possible transformations of MAC from LAMN within a single tumor, different from those that occurred during the recurrent process of the tumor [30].…”
Section: Discussionsupporting
confidence: 53%
“…Davison et al 14 found that any of the following confer a worse prognosis in PMP of appendiceal origin: destructive invasion, high cytologic grade, high tumor cellularity, angiolymphatic invasion, perineural invasion, and signet ring cells. These features were used to classify lesions into 3 grades: G1 lacks all of these features; G2…”
Section: Discussionmentioning
confidence: 98%
“…[1][2][3][4][5][6][7][8][13][14][15][16][17]22,34 With the development of curative treatment for PMP based on cytoreductive surgery and perioperative intraperitoneal chemotherapy, it is essential to harmonize terminology and diagnostic criteria, not only for the management of individual patients but also to allow comparison between institutions and different surgical techniques which can profoundly affect outcomes. 16,22,35 Cytoreductive surgery and perioperative intraperitoneal chemotherapy are now considered a standard of care for PMP, 36 and prognostic assessments from histopathology performed at institutions not using this technique must be approached with caution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations